Antimicrobial and antioxidant activity of proteins from Feijoa sellowiana Berg. fruit before and after in vitro gastrointestinal digestion. Issue 18 (16th September 2020) - Piscopo, Marina; Tenore, Gian Carlo; Notariale, Rosaria; Maresca, Viviana; Maisto, Maria; de Ruberto, Francesca; Heydari, Milad; Sorbo, Sergio; Basile, Adriana
Abstract: In this paper we report for the first time a method for the extraction of the protein fraction from Feijoa sellowiana Berg. fruit and its electrophoretic analysis. In addition we analyzed the protein fraction for its antioxidant activity and its effectiveness against different Gram-positive and Gram-negative bacteria both as American type culture collection (ATCC) standard and clinically isolated strains. Both antimicrobial and antioxidant activity resulted stronger respect to that previously obtained for the acetonic extract from the same fruit. Further, we study both activities also on the product of in vitro gastrointestinal digestion of F. sellowiana fruit proteins. The results showed that in vitro gastrointestinal digestion increased 10 fold the antioxidant activity, while the antimicrobial activity, tested only on ATCC strains, resulted from 2 to 4 fold increased. MTT assays showed the non-toxicity of these proteins both before and after digestion. Graphical Abstract: